2015
DOI: 10.1353/cpr.2015.0029
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Screening Utilization Among Immigrant Women in Miami, Florida

Abstract: Given the disparities in cancer screening between our samples and the larger sociodemographic groups in which they are often included, targeted approaches that address structural barriers (lack of health insurance or usual source of care) may improve access to cancer screening among recent immigrants. Community partnerships may be essential in facilitating the interventions needed to overcome cancer-related disparities in these groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Our findings on patient acceptability of HPV self-sampling are consistent with data among other vulnerable groups and similar to our prior findings among a community-based sample of Haitian women. 37,[40][41][42][43][44] We also found that Haitian women at CHS were more likely to choose HPV self-sampling than Latinas at ACC. Our prior work has shown that Haitian women have much less familiarity and experience with Pap smear than Latinas.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Our findings on patient acceptability of HPV self-sampling are consistent with data among other vulnerable groups and similar to our prior findings among a community-based sample of Haitian women. 37,[40][41][42][43][44] We also found that Haitian women at CHS were more likely to choose HPV self-sampling than Latinas at ACC. Our prior work has shown that Haitian women have much less familiarity and experience with Pap smear than Latinas.…”
Section: Discussionsupporting
confidence: 54%
“…Our prior work has shown that Haitian women have much less familiarity and experience with Pap smear than Latinas. [42][43][44] However, financial considerations may have also played a role in why more Haitian women chose HPV; at CHS women have to pay separately for a Pap smear (based on a sliding fee scale) while at ACC the service is included when done as part of the visit. We also found that HPV prevalence among the participants varied by ethnicity with Haitian participants demonstrating a higher prevalence than Latinas, whose prevalence was notably lower than previously measured in a national sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles by Seay and colleagues 6 and Shirazi and colleagues 7 address screening in groups ranging from Haitian and Cuban immigrants in Miami to breast cancer screening in Afghan women in Alameda County, California, rural Latina and American-Indian women in Kansas, and urban African-American women in Baltimore. Meade and colleagues 8 present an interesting description of introducing the concept of biospecimen collection in Tampa and Buffalo.…”
Section: Cnp Comprehensive Centersmentioning
confidence: 99%
“…When compared to other racial/ethnic minority and immigrant groups in the Miami metropolitan area, Haitian and Hispanic women contribute disproportionately to cervical cancer incidence, morbidity and mortality, largely as a function of their underutilization of Pap smear screening [7–10]. They do not receive routine Pap smears for myriad reasons including but not limited to: poverty, language difficulties, limited access to health care, lack of knowledge about cancer and the importance of early detection, cancer fatalism or the belief that cancer implies death, and cultural norms about health and about disease prevention [7, 1118]. …”
Section: Introductionmentioning
confidence: 99%